Serologic Evidence of Chicken Infectious Anemia in Commercial Chicken Flocks in Shahrekord, Iran - Mahzounieh, M.; Karimi, I.; Salehi, T. Zahraei (International Journal of Poultry Science, 2005)
CIAV infection in chicken flocks has been described in most countries with a developed chicken industry and can result in economically important clinical or subclinical disease in broiler chickens. In this study sera samples from 46 poultry flocks in Sharekord area, Iran, were tested for the presence of chicken infectious anemia virus (CIAV) antibodies using a commercial enzyme-linked immunosorbent assay kit. All farms were positive for CIAV antibodies and 87.7% of chickens were positive. The prevalence of seropositivity was always over 20% (average 87.7%). Rates of antibody-positive chickens among flocks ranged from 20% to 100%. Seroprevalence was higher within the older flocks than in the younger flock. This is the first report of serologic evidence of CIAV in Shahrekord province, Iran. Since Shahrekord located in the center of Iran and one day chickens imported form other provinces, the infection can probably be found throughout the country and beyond. Further studies are necessary to assess economic losses due to CIAV and the cost benefit of countermeasures.